Emulsion Cross-Linking Technique for Human Fibroblast Encapsulation - Watcharaphong Chaemsawang; Weerapong Prasongchean; Konstantinos I. Papadopoulos; Suchada Sukrong; W. John Kao; Phanphen Wattanaarsakit (International Journal of Biomaterials)
Microencapsulation with biodegradable polymers has potential application in drug and cell delivery systems and is currently used in probiotic delivery. In the present study, microcapsules of human fibroblast cells (CRL2522) were prepared by emulsion cross-linking technique. Tween 80 surfactant at a 2% concentration through phase inversion resulted in the most efficient and stable size, morphology, and the cells survival at least 50% on day 14. Emulsion cross-linking microcapsule preparation resulted in smaller and possibly more diverse particles that can be developed clinically to deliver encapsulated mammalian cells for future disease treatments.